1996
DOI: 10.1161/01.cir.94.7.1613
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Repeated Intravenous Doses of Ibutilide for Rapid Conversion of Atrial Flutter or Fibrillation

Abstract: Intravenous ibutilide given in repeated doses is effective in rapidly terminating atrial fibrillation and flutter and under monitored conditions is an alternative to current cardioversion options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
231
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(254 citation statements)
references
References 47 publications
17
231
0
6
Order By: Relevance
“…Alternatywny lek to ibutilid, jeżeli jest on dostępny, ale jego stosowanie wiąże się z ryzykiem wystąpienia torsade de pointes [615]. Wernakalant [602][603][604][605] można podawać pacjentom z mało nasiloną niewydolnością serca (I lub II klasa wg NYHA), włącznie z pacjentami z chorobą niedokrwienną serca, pod warunkiem że nie stwierdza się u nich niskich wartości ciśnienia tętniczego ani ciężkiej stenozy aortalnej [616][617][618].…”
Section: Leki Antyarytmiczne W Celu Doraźnego Przywracania Rytmu Zatounclassified
“…Alternatywny lek to ibutilid, jeżeli jest on dostępny, ale jego stosowanie wiąże się z ryzykiem wystąpienia torsade de pointes [615]. Wernakalant [602][603][604][605] można podawać pacjentom z mało nasiloną niewydolnością serca (I lub II klasa wg NYHA), włącznie z pacjentami z chorobą niedokrwienną serca, pod warunkiem że nie stwierdza się u nich niskich wartości ciśnienia tętniczego ani ciężkiej stenozy aortalnej [616][617][618].…”
Section: Leki Antyarytmiczne W Celu Doraźnego Przywracania Rytmu Zatounclassified
“…24) With respect to its mechanism of action, ibutilide has been shown to activate the slow inward Na + current 25) and to block the rapidly activating delayed rectifier K + current. 26) Previous work from our laboratory has shown that intravenous administration of ibutilide in patients without AF significantly increases RA MAPD and the ERP at pacing CLs of 600 and 350 ms in a weak reverse ratedependent manner and that IACT does not change at pacing CLs of 600 and 350 ms (Table IV).…”
Section: Effects Of Class III Antiarrhythmic Drugs In the Remodeled Hmentioning
confidence: 99%
“…It prolongs the action potential duration and effective refractory periods in both the atria and the ventricles. [1][2][3][4][5] In previous studies, ibutilide significantly prolonged the QTc interval in ECG studies in healthy volunteers and patients with AF or AFl. [2][3][4][5] This effect was dose related and correlated directly with plasma ibutilide concentrations.…”
Section: Ibutilide-induced Repolarization Alterationsmentioning
confidence: 99%
“…[1][2][3][4][5] In previous studies, ibutilide significantly prolonged the QTc interval in ECG studies in healthy volunteers and patients with AF or AFl. [2][3][4][5] This effect was dose related and correlated directly with plasma ibutilide concentrations. 3 In this study, although QT maximum, QT minimum, and QT dispersion significantly increased from baseline to the postinfusion ECG in Group 1 patients, QTc maximum failed to demonstrate significant changes from the first to the second ECG.…”
Section: Ibutilide-induced Repolarization Alterationsmentioning
confidence: 99%
See 1 more Smart Citation